An emissions-based fuel mass loss measurement for wood-fired hydronic heaters. (November 2020) - Weisberger, Joshua M.; Richter, Joseph P.; Mollendorf, Joseph C.; DesJardin, Paul E.
Abstract: Regulations that standardize the evaluation of wood-fired hydronic heaters (WHH) use mass loss as an important variable to compute energy input. Generally, mass loss is measured by placing the entire appliance on a scale and measuring the system mass change. This method suffers from resolution problems since the change in mass of the fuel during a run is much smaller than the total mass of the empty appliance. This experimental study provides a higher-resolution measurement of mass loss by measuring the concentration of flue gas emissions in addition to the flow rate of air into the WHH. Three fuels (red oak, cherry, and pine) are independently tested, and measurements of the emissions are made using both a Testo gas analyzer and tunable diode laser absorption spectroscopy. A simultaneous direct measurement of the mass loss is performed using a hanging basket inside the WHH, and the average percent difference between the two methods are 5.4 % for red oak, 5.4 % for cherry, and 8 % for pine, indicating that the emissions-based method is suitable for mass loss measurements. Highlights: A new non-intrusive measurement of fuel mass loss rate for hydronic heaters using emission concentrations and an air flow measurement. Measurement approach validated with in-situ direct measurement of fuel mass for a practical two-stage hydronic heater. Method explored using three different wood fuels that have distinctly different chemical signatures. The benefits of the emissions-based fuel mass measurements are that it is non-intrusive and that it provides the same accuracy and better precision than a full-appliance scale. This combined diagnostic approach could supplement current methods of fuel mass loss rate measurements used for certification of these appliances.